Expression of the Style of Expression with Philosophical and Symbolic Signs in Isajan Sulton's Novel "Genetic" - Maksutbaeva Nigora Rashid qizi (International Journal of Scientific Trends, 2024)
This article contains views on the formation of style and form in the works of Isajon Sultan in different styles. In Isajon Sultan's works, it is related to the relationship of the artistic form with the content, the system of images, plot lines, and forms of conflicting relationships. The composition of the work is related to people with different characters and characteristics and the structure of the composition of the work. In this regard, it is based on the elevation of symbolism and figurativeness to the level of symbols and forms of narrative with the style of epic imagery. Comparing the works of Isajon Sultan and Khurshid Dost Mohammad with each other or with artists like Shukur Kholmirzayev leads to the poetic development of the same topic. Different aspects of Isajon Sultan's works depicting simple life and romantic themes can be mentioned. In this regard, the postmodernist style and forms of communication in the novel also appear. In the creation of the work, there is a connection between poetic thinking and Roman epics. In the novels of Isajon Sultan, the development of the characters and events occurs due to the addition of certain events, dates or personalizations. There is also a lyrical digression, a relationship between the subject and the object.